Expressing GMoDS Models into Object-Oriented Models Using the Event-B Language (Informatica, 2016)
Among the agent-oriented methodologies that use goals for specication of multi-agent systems, the Goal Model for Dynamic Systems (GMoDS) method allows to specify goals during requirements engineering process and then to use them throughout the system development and at runtime. Because the semantics of the GMoDS models involves the use of object-oriented concepts we choose to express a GMoDS model in an object-oriented specication. We use Event-B as a method for both specifying the GMoDS models and implementing the semantics of the runtime model of GMoDS. Because Event-B is not an object-oriented language, the goal of our research is to add support to Event-B for object-oriented modeling by using the modularization plug-in of the Rodin framework. This aim of paper is twofold: (a) to describe an object-oriented specication in Event-B, and (b) to express a GMoDS model into an object-oriented Event-B specication.